2021
DOI: 10.1108/sbm-06-2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

Sports celebrity personality and purchase intention: the role of endorser-brand congruence, brand credibility and brand image transfer

Abstract: PurposeThis study aims to examine the influence of five sports celebrity personality (SCP) attributes – attractiveness, expertise level, credibility, trustworthiness and character – on consumers' purchase intentions (CPI). It identifies celebrity brand congruence (CBC), endorsed brand celebrity (EBC) and transfer of brand image (TBI) as antecedents of CPI.Design/methodology/approachThe purposive sampling technique was used to collect the data from 838 respondents. This study developed a multidimensional constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 68 publications
3
25
0
3
Order By: Relevance
“…Kabiraj and Shanmugan (2011), Ahmed and Moosavi (2013), Can and Erdil (2018) and Abitbol and Sternadori (2019) express similar results that brand loyalty affects purchase intention positively. Martin-consuegra et al (2018), Monoarfa and Tausyanah (2020), and Rai et al (2021) express similar results that brand credibility affects purchase intention positively too. Finally, both brand credibility (Dwivedi, Nayeem and Murshed, 2018;Herjanto, Adiwijaya, Wijaya and Semuel, 2020) and brand loyalty (Kim, Wang andAhn, 2013, Ndlela andChuchu, 2016) are mediators between celebrity endorsement and purchase intention as expressed in similar researches.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 65%
“…Kabiraj and Shanmugan (2011), Ahmed and Moosavi (2013), Can and Erdil (2018) and Abitbol and Sternadori (2019) express similar results that brand loyalty affects purchase intention positively. Martin-consuegra et al (2018), Monoarfa and Tausyanah (2020), and Rai et al (2021) express similar results that brand credibility affects purchase intention positively too. Finally, both brand credibility (Dwivedi, Nayeem and Murshed, 2018;Herjanto, Adiwijaya, Wijaya and Semuel, 2020) and brand loyalty (Kim, Wang andAhn, 2013, Ndlela andChuchu, 2016) are mediators between celebrity endorsement and purchase intention as expressed in similar researches.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 65%
“…When the expertise of the broadcaster as a source of information increases, the credibility of the broadcaster’s information output is enhanced, and consumer identification with the product is thus strengthened ( Rai et al, 2021 ). In live streaming, the expertise of the information source refers to the ability of the broadcaster to provide accurate and detailed information based mainly on the broadcaster’s in-depth knowledge and understanding of the recommended products.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Ilicic and Webster (2013) also suggested that consumers might form their belief in the consistency of the celebrity endorser in providing information regarding the product brand and brand benefits. Recently, Rai et al (2021) identified congruence between a sport celebrity and a brand has a positive impact on image transfer from the celebrity to the brand. In this sense, the positive relationship between athlete celebrity-product fit and image transfer is expected.…”
Section: Perceived Product Class Fitmentioning
confidence: 99%